2014
DOI: 10.1002/anie.201404556
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Heterolytic OO Bond Cleavage of Putative Nonheme Iron(II)OOH(R) Complexes for Fenton and Enzymatic Reactions

Abstract: One-electron reduction of mononuclear nonheme iron(III) hydroperoxo (Fe(III)-OOH) and iron(III) alkylperoxo (Fe(III)-OOR) complexes by ferrocene (Fc) derivatives resulted in the formation of the corresponding iron(IV) oxo complexes. The conversion rates were dependent on the concentration and oxidation potentials of the electron donors, thus indicating that the reduction of the iron(III) (hydro/alkyl)peroxo complexes to their one-electron reduced iron(II) (hydro/alkyl)peroxo species is the rate-determining ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…A Hammett plot of the second-order rate constants vs σ p + gave a ρ value of −5.0 (Figure 4b, left panel; SI, Table S1), confirming the electrophilic character of the hydroperoxo group in 2 . 16 In addition, we observed a good linear correlation when the rates were plotted against oxidation potentials ( E ox ) of thioanisoles (Figure 4b, right panel; SI, Table S1). The negative slope of −17 for 2 is significantly larger than that obtained in the sulfoxidation reaction by Fe III –hydroperoxo (slope = −2.5).…”
mentioning
confidence: 64%
“…A Hammett plot of the second-order rate constants vs σ p + gave a ρ value of −5.0 (Figure 4b, left panel; SI, Table S1), confirming the electrophilic character of the hydroperoxo group in 2 . 16 In addition, we observed a good linear correlation when the rates were plotted against oxidation potentials ( E ox ) of thioanisoles (Figure 4b, right panel; SI, Table S1). The negative slope of −17 for 2 is significantly larger than that obtained in the sulfoxidation reaction by Fe III –hydroperoxo (slope = −2.5).…”
mentioning
confidence: 64%
“…In line with the observations made in natural systems, the CpdI analogues in model systemsa re better formed under acidic conditions which trigger the O-O lysis of aF e III (OOH) precursor. [31][32][33][34] According to theoretical studies, OÀOc leavage is also affected by the spin state on the iron(III) center.D FT calculations performed by Solomon and co-workers suggested that OÀOb ond homolysis in S = 5/2 systems is % 10 kcal mol À1 higher in energy than in the low-spin counterparts (S = 1/2). [22][23][24][25][26][27][28][29] Direct evidence for this process was gained by Que and co-workers, who reported the water-assisted heterolytic OÀOc leavage in [Fe III (OOH)(solvent)(tpa)] 2 + (tpa = tris(2-pyridylmethyl)amine, solvent = H 2 Oo rM eCN) leading to the formation of ah igh valent Fe V (O) species.…”
Section: Introductionmentioning
confidence: 99%
“…14 Especially in the eld of iron-based, bioinspired oxidation catalysis remarkable advances were made in the last decade, leading to a better understanding of reaction mechanisms and to improved catalyst performance. 13,[15][16][17] A common structural motif of these compounds is the use of polydentate ligands with N donor atoms as supporting ligands for Fe(II) and Fe(III) complexes. 13,18 Furthermore, the successful implementation of N-heterocyclic carbenes (NHCs) as ligands to a range of transition metal-catalyzed reactions also led to a constantly increasing number of reported iron NHC complexes with catalytic activity.…”
Section: Introductionmentioning
confidence: 99%